Factores de riesgo y su relación con el desarrollo de diabetes mellitus tipo 2 en adultos mayores atendidos en el Hospital General Guasmo Sur. Periodo junio – octubre 2023. - Monserrate Gamarra, Soraya Cristina (2023)
Type 2 diabetes is believed to prevail in an individual due to an interaction between various lifestyles, medical conditions, hereditary, psychosocial, and demographic risk factors, such as elevated serum uric acid levels, quality/amount of sleep, smoking, depression, cardiovascular disease, dyslipidemia, hypertension, aging, ethnicity, family history of diabetes, physical inactivity, and obesity. However, there is no study at the local level that determines this, therefore, the research will allow obtaining an evaluation of the risk factors and their relationship with the development of type 2 diabetes mellitus in older adults treated at the Guasmo General Hospital. South. Period June – October 2023. Aim: Determine the risk factors and their relationship with the development of type 2 diabetes mellitus in older adults treated at the Guasmo Sur General Hospital. Period June – October 2023. Methodology: The research is quantitative, descriptive, and cross-sectional. Results: A prevalence of 69% of type 2 diabetes mellitus was obtained in older adults treated at the Guasmo Sur Hospital, which means that, currently, there is still a high prevalence of this disease. Regarding lifestyle, it was found that older adults follow self-care guidelines by regularly going to laboratory checkups, visiting the dentist, taking their medications, and following their diet. However, the main risk factors found associated with the presence of type 2 diabetes mellitus were sedentary lifestyle and advanced age.